Bilateral hypertrophic olivary degeneration in genetic neurological disorders - Aleksander S. Suslin; Yury A. Seliverstov; Elena I. Kremneva; Marina V. Krotenkova (Анналы клинической и экспериментальной неврологии, 2020)
Hypertrophic olivary degeneration (HOD) is a rare variant of transsynaptic degeneration in the inferior olivary nuclei due to a lesion within the dentato-rubro- olivary pathway, also known as the GuillainMollaret triangle. Bilateral HOD can be identified on MRI in patients with not only acquired but also genetic neurological disorders. The article describes patients with both common and rare genetic causes of the bilateral HOD. The pathophysiology of HOD is also briefly reviewed.